Nilai dan Fungsi Tarian Gawe Daku Masyarakat Desa Bahinga Kecamatan Tanjung Bunga Kabupaten Flores Timur - Maria Felisitas Nitit Maran; Imelda Oliva Wissang; Pilipus Wai Lawet (Social Science Academic, 2023)
This study aims to describe the values and functions of the Gawe Daku dance in Bahinga Village, Tanjung Bungan District, East Flores Regency. Gawe Daku dance, is a traditional Lamaholot dance, a traditional dance with movements that appear as spontaneous movements that do not have specific rules but still have a clear foundation, so they still look orderly and orderly. To achieve the research objectives above, a research approach is used, namely a qualitative approach using descriptive research types. The research location is Bahinga Village. Data collection techniques used are observation, interviews and documentation. Checking the validity of the data using triangulation techniques. The results of this study state that there are values in the Gawe Daku dance. a) shared values. b) the value of unity. c) family values. d) the value of beauty, and the function of the Gawe Daku dance. a) as a means of ceremony. b) as a means of entertainment. c) as a means of performance, and d) as a means of education.